Usefulness of co-treatment with immunomodulators in patients with inflammatory bowel disease treated with scheduled infliximab maintenance therapy. Issue 10 (29th June 2010) - Sokol, Harry; Seksik, Philippe; Carrat, Fabrice; Nion-Larmurier, Isabelle; Vienne, Ariane; Beaugerie, Laurent; Cosnes, Jacques
Abstract : Background and aims: Concomitant use of immunosuppressants (IS) with scheduled infliximab (IFX) maintenance therapy for Crohn's disease (CD) or ulcerative colitis (UC) is debated. The aim of this study was to assess whether IS co-treatment is useful in patients with inflammatory bowel disease (IBD) on scheduled IFX infusions. Methods: 121 consecutive patients with IBD (23 UC, 98 CD) treated by IFX and who received at least 6 months of IS co-treatment (azathioprine (AZA) or methotrexate (MTX)) were studied. In each patient, the IFX treatment duration was divided into semesters which were independently analysed regarding IBD activity. Results: Semesters with IS (n=265) and without IS (n=319) were analysed. IBD flares, perianal complications and switch to adalimumab were less frequently observed in semesters with IS than in those without IS (respectively: 19.3% vs 32.0%, p=0.003; 4.1% vs 11.8%, p=0.03; 1.1% vs 5.3%, p=0.006). Maximal C-reactive protein (CRP) level and IFX dose/kg observed during the semesters were lower in semesters with IS. Within semesters with IS, IBD flares and perianal complications were less frequently observed in semesters with AZA than in those with MTX. In multivariate analysis, IS co-treatment was associated with a decreased risk of IBD flare (OR 0.52; 95% CI 0.35 to 0.79) Conclusion: In patients with IBD receiving IFX maintenance therapy, IS co-treatment is associated with reduced IBD activity, IFX dose and switch to adalimumab. In this setting, co-treatment with AZA seems to be more effective than co-treatment with MTX. Benefit of such a combination treatment has to be balanced with potential risks, notably infections and cancers.